Problematic Domains of Romantic Relationships as a Function of Attachment Insecurity and Gender. Issue 1 (9th March 2020) - Muetzelfeld, Hannah; Megale, Allison; Friedlander, Myrna L.
Abstract : Theoretically, securely attached adults view the world as safe and see their romantic partners as emotionally available, supportive, and non‐threatening. Little is known, however, about which relationship domains are most problematic for securely (versus insecurely) attached adults. To fill this gap, we asked 62 adults in committed relationships to complete the Marital Satisfaction Inventory‐Revised (MSI‐R; Snyder, 1997), a measure of the frequency and severity of 10 kinds of couple problems, and the Experiences in Close Relationships‐Revised (ECR‐R; Fraley, Waller, & Brennan, 2000), a measure of attachment insecurity. High Avoidance and Anxiety were associated with numerous relationship problems being rated as frequent and severe. A canonical correlation showed that 26.5% of the variance in the set of relational problem areas was accounted for by attachment insecurity and gender. While greater attachment security was associated with fewer perceived difficulties in affective communication, irrespective of gender, greater Avoidance and Anxiety were associated with more difficulties in this area. Female participants with high Anxiety (and low Avoidance) reported more global relationship and family‐of‐origin distress, but fewer financial disagreements and less difficult problem‐solving communication; conversely, male participants with high Avoidance (and low Anxiety) reported more financial disagreements and difficult problem‐solving communication, but less global relationship and family‐of‐origin distress. These results have implications for practice by suggesting ways in which couples' attachment dynamics can become manifested in specific kinds of relational difficulties.